A Retrospective Look at Rescuing and Restructuring General Motors and Chrysler - Austan D. Goolsbee; Alan B. Krueger (Institute for the Study of Labor (IZA), 2015)
This paper takes a retrospective look at the U.S. government's effort to rescue and restructure General Motors and Chrysler in the midst of the 2009 economic and financial crisis. The paper describes how two of the largest industrial companies in the world came to seek a bailout from the U.S. government, the analysis used to evaluate their request, and the steps taken by the government to rescue them. The paper also summarizes the performance of the U.S. auto industry since the bailout and draws some general lessons from the episode.
Keywords: H0; L50; L62; G01; G33; 330; auto bailout; auto industry